1995
DOI: 10.1046/j.1420-9101.1995.8020129.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of female mate preferences

Abstract: We review the evidence for genetic variation in female and male mate preferences. Genetic differences between species and partially isolated races show that preferences can evolve and were genetically variable in the past. Within populations there is good evidence of genetic variation, both of discrete genetic effects (8 cases) and quantitative genetic effects (17 cases), from a diverse range of taxa. We also review evidence for the presence of genetic covariance between mate preferences and sexual traits in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
184
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(191 citation statements)
references
References 142 publications
(204 reference statements)
5
184
1
Order By: Relevance
“…Under the assumption that pleiotropy between female preference genes and genes contributing to productivity is negligible (Lande 1981;Bakker & Pomiankowski 1995), female choice for male genetic quality appears to have generated linkage disequilibrium between preference genes and offspring fitness genes, as predicted by models of good genes' sexual selection (Iwasa et al 1991;Kirkpatrick & Barton 1997). The level of genetic correlation between female preference and offspring fitness detected was small, indicating that the strength of indirect selection on female preference generated by the positive association between preference and fitness genes may be relatively weak (Kirkpatrick & Barton 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Under the assumption that pleiotropy between female preference genes and genes contributing to productivity is negligible (Lande 1981;Bakker & Pomiankowski 1995), female choice for male genetic quality appears to have generated linkage disequilibrium between preference genes and offspring fitness genes, as predicted by models of good genes' sexual selection (Iwasa et al 1991;Kirkpatrick & Barton 1997). The level of genetic correlation between female preference and offspring fitness detected was small, indicating that the strength of indirect selection on female preference generated by the positive association between preference and fitness genes may be relatively weak (Kirkpatrick & Barton 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, genetic associations among traits conferring reproductive isolation, in the forms of linkage disequilibrium, physical linkage, and pleiotropy, can facilitate divergence by transferring the effects of natural and sexual selection on some traits to others, resulting in the coordinated evolution of a suite of characteristics that together limit mating between incipient species (11)(12)(13)(14)(15). Genetic linkage of sexual isolating traits is particularly widespread in Lepidoptera, where a disproportionately large number of traits distinguishing closely related species are sex-linked (16)(17)(18).…”
mentioning
confidence: 99%
“…Although the phenotypic con-sequences of female preference are well described (Jennions and Petrie 1997), much less is known about the genetic basis of female preferences and, subsequently, how female preferences evolve. A number of studies have demonstrated that female preference is heritable (Bakker and Pomiankowski 1995;Jennions and Petrie 1997;Chenoweth and Blows 2006), but the inherent difficulties in quantifying mating preferences (Wagner 1998;Chenoweth and Blows 2006) have limited the application and scope of quantitative genetic experiments on such traits.…”
mentioning
confidence: 99%